2011
DOI: 10.1186/1756-3305-4-96
|View full text |Cite
|
Sign up to set email alerts
|

No Paragonimus in high-risk groups in Côte d'Ivoire, but considerable prevalence of helminths and intestinal protozoon infections

Abstract: BackgroundParagonimiasis is a neglected tropical disease caused by an infection with lung flukes that is transmitted through the consumption of undercooked crabs. The disease is often confused with tuberculosis. Paragonimiasis is thought to be endemic in south-western Côte d'Ivoire.MethodsTwo cross-sectional surveys were carried out in the first half of 2009 in patients attending two tuberculosis centres of Abidjan. A third cross-sectional survey was conducted in May 2010 in children of two primary schools in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
7
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 29 publications
5
7
2
Order By: Relevance
“…The overall prevalence of intestinal helminths (21.3%) and STHs (19.5%) found in this study is lower than most results obtained in studies of school-aged children across the country [18, 19]. However, our results were higher than those of few community surveys.…”
Section: Discussioncontrasting
confidence: 92%
“…The overall prevalence of intestinal helminths (21.3%) and STHs (19.5%) found in this study is lower than most results obtained in studies of school-aged children across the country [18, 19]. However, our results were higher than those of few community surveys.…”
Section: Discussioncontrasting
confidence: 92%
“…intestinalis remains the predominant pathogenic intestinal protozoon with an overall prevalence above 10% in all three departments. Meanwhile, non-pathogenic intestinal protozoa species, namely E. coli and E. nana , showed the highest prevalence, corroborating previous studies conducted in different parts of Côte d’Ivoire ( Coulibaly et al, 2012 ; Ouattara et al, 2010 ; Traoré et al, 2011 ). Although these are non-pathogenic protozoa, it highlights the high faecal contamination of the community surroundings ( Savichtcheva and Okabe, 2006 ).…”
Section: Discussionsupporting
confidence: 89%
“…Similar results were found by Mohammed Mahady and colleagues in Malaysia [30]. On the other hand, Traoré et al , in a study carried out in school-aged children in Côte d’Ivoire, reported a considerably higher prevalence of intestinal protozoa among boys than girls [31], corroborating findings by Cifuentes et al from Mexico, where boys were at higher odds of a G. intestinalis infection that girls [32]. Other studies found no gender difference at all [33].…”
Section: Discussionsupporting
confidence: 80%